Design, construction, and expression of recombinant human interferon beta gene in CHO-s cell line using EBV-based expression system - Mohadeseh Shayesteh; Fahimeh Ghasemi; Fatemeh Tabandeh; Bagher Yakhchali; Mehdi Shakibaie (Research in Pharmaceutical Sciences, 2020)
Background and purpose: Codon optimization has been considered as a powerful strategy to increase the expression level of protein therapeutics in mammalian cells. As an empirical approach to study the effects of the codon usage and GC content on heterologous gene expression in suspension adapted Chinese hamster ovary (CHO-s) cells, we redesigned the recombinant human interferon beta (rhIFN- β) gene based on the codon preference of the CHO cell in a way to increase the GC content in the third position of each codon. Experimental approach: The nucleotide sequence of the codon-optimized rhIFN-β was synthesized in parallel with the wild-type and expressed transiently inCHO-s cells using Epstein-Bar virus (EBV)-based expression system. The protein expression of the rhIFN-β by codon-optimized and wild-type genes were quantified using ELISA test. Findings / Results: The results indicated a 2.8-fold increase in the expression level of the biologically active form of the rhIFN-β by codon-optimized sequence. Conclusion and implications: These results shed light on the capability of codon optimization to create a stable CHO cell for scaling up the production of recombinant therapeutics such as rhIFN-β.